EVALUASI PENERAPAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) PADA PROYEK GEDUNG MASJID KINIBALU SAMARINDA - MEIYN GAYI DUTHIE, TRISTINA APRILLIA (KURVA S JURNAL MAHASISWA, 2020)
Based on the problems found, namely how the Application of Occupational Safety and Health (K3) in the construction of the Mosque building in Kinibalu ? the purpose of this study is this thesis is as follow : knowing the Application of Occupational Safety and Health (K3) in the construction of the mosque kinibalu Samarinda City building. Occupational Safety and health is an approach that sets comprehensives and specific standars, determines government policies on company practices in the workplaces and is implemented through court letters, fines and other laws. From the results of the discussion it was concluded that the importance of the Application of Occupational Safety and Health (K3) in the construction if the Mosque of Kinibalu.                This research suggestion is in the implementation of the necessary K3  Management training so that all responsible parties in the company have sufficient ability and know about K3 management